Proceedings of the Graduate Research in Education Seminar (GREduc) 2021 - Faculty of Educational Studies (Faculty of Educational Studies, 2021)
The Graduate Research in Education Seminar (GREduc) 2021, held on 18 December 2021 and organized by the Faculty of Educational Studies, focused on the theme Envisioning Education and Human Resource Development in the 21st Century through Research and Innovation.